Fresh versus frozen embryo transfer: a retrospective cohort study - Shetty, Raksha K.; Nadkarni, Purnima K.; Singh, Pooja P.; Singh, Prabhakar; Nadkarni, Aditi A.; Nadkarni, Vaibhav K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Elective frozen embryo transfer (FET), has recently increased significantly with improvements in cryopreservation techniques. Observational studies and randomized controlled trials suggested that the endometrium in stimulated cycles is not optimally prepared for implantation; risk of ovarian hyperstimulation syndrome reduced and pregnancy rates increased following FET and perinatal outcomes are less affected after FET. However, the evidence is not unequivocal and recent randomised control trials challenge the use of elective FET for the general IVF population. Pregnancy rates were analysed in a cohort of patients undergoing embryo transfers. Methods: This was a retrospective cohort study of patients who underwent embryo transfers from April 2018 to March 2019 at study centre in Surat.175 cycles of embryo transfers (119 fresh and 56 frozen) were included in the study. Outcomes measured were positive pregnancy, clinical pregnancy and ongoing clinical pregnancy rates achieved in the IVF-ET cycles. Results: There were no statistically significant differences between positive pregnancy rate (54.6% versus 60.7%, Odds ratio (OR) 0.78; 95% Confidence Interval (CI) 0.41-1.49), clinical pregnancy rate (48.73% versus 57.14%, OR 0.52; 95% CI 0.1- 2.64) and ongoing clinical pregnancy rate (45.38% versus 51.78% OR 1.4; 95% CI 0.29 - 6.67) in fresh ET and FET cycles, respectively, p < 0.05 was considered statistically significant for all measures. Conclusions: Despite the observed higher rates of positive biochemical, clinical and ongoing clinical pregnancy per transfer in the FET cohort, these did not reach statistical significance. Thus, both transfer strategies are reasonable options, although there is a trend favouring the freeze-all strategy.